Synthesis, Characterization, Biological Activity of Novel 1H-benzo[f]- chromene and 12H-benzo[f]chromeno[2,3-d]pyrimidine Derivatives - Abd El-Mawgoud, Heba K.; Radwan, Hebat Allah M.; El-Mariah, Fatma; El-Agrody, Ahmed M. (Letters in Drug Design & Discovery, 2018)
Background: Chromene, benzochromene and their derivatives have been considered as an important class of oxygen-containing heterocycles. There has been increasing interest in the study of chromenes and benzochromenes due to their biological and pharmacological activities. Methods: 3-Amino-1-(4-chlorophenyl)-9-hydroxy-1H-benzo[f]chromene-2-carbonitrile (3) was used as precursor for the synthesis of novel 1H-benzo[f]chromene (4,8-11) and 12Hbenzo[ f]chromeno[2,3-d]pyrimidine (5-7,12-14) derivatives via reaction of compounds 3 with appropriate chemical reagents. The structures of the synthesized compounds were confirmed on the basis of spectral data, IR, 1H NMR, 13C NMR and MS data. The targeted compounds were tested in-vitro for their antimicrobial activity and showed congruent results against the most tested microorganisms compared to the standard drugs Gentamycin and Ketoconazol. The Structure Activity Relationship (SAR) study for the target compounds agreed with the in-vitro essays and confirmed higher potent antimicrobial activity against some of the tested microorganisms. Results: In this study, the antimicrobial activity of the synthesized compounds 3–14 was examined and showed congruent results against the most tested microorganisms compared to the standard drugs Gentamycin and Ketoconazol. Conclusion: Several 1H-benzo[f]chromene (4,8-11) and 12H-benzo[f]chromeno[2,3-d]- pyrimidine (5-7,12-14) derivatives were synthesized in good yields, starting from β-enaminonitrile 3 and elucidated on the basis of spectral data. An antimicrobial study has been performed and some compounds showed congruent results against the most tested microorganisms compared to the standard drugs Gentamycin and Ketoconazol.
Keywords: gentamycin